Virome analysis and detection of ticks and tick-borne viruses in Shanghai, China - Zeng, Wenbo; Yang, Limin; Cui, Lei; Liang, Chuhan; Zhu, Dan; Fang, Yuan; Zhang, Yi; Liu, Hongxia (Frontiers in Microbiology, 2025)
IntroductionTicks are well-known ectoparasites and vectors responsible for transmitting a diverse range of pathogens, including viruses, bacteria, and protozoa, many of which pose substantial risks to public health and livestock. In recent decades, the incidence and diversity of tick-borne diseases have increased globally, with several novel tick-borne viruses (TBVs) being discovered.MethodsThis study aimed to characterize the virome of ticks collected from various locations in Shanghai, China, using next-generation sequencing (NGS). A total of 2,568 ticks belonging to three dominant species—Haemaphysalis flava, Haemaphysalis longicornis, and Rhipicephalus sanguineus sensu lato—were collected and analyzed through metagenomic sequencing.ResultsThe sequencing analysis identified 214 viral contigs classified into 32 viral families, including Chrysoviridae, Phenuiviridae, Partitiviridae, Nairoviridae, Dicistroviridae, Reoviridae, Botourmiaviridae, and Flaviviridae. Several TBVs with potential relevance to human and animal health, such as Cheeloo Jingmen-like virus (CJLV), Songling virus (SGLV), brown dog tick phlebovirus 1 (BDTPV1), brown dog tick phlebovirus 2 (BDTPV2), and Wuhan mosquito virus 1 (WMV1), were detected. Significant differences in virome composition among tick species based on geographical locations were also observed.DiscussionThese findings highlight the influence of environmental factors on viral diversity in ticks and underscore the need for ongoing surveillance of TBVs. Implementation of longitudinal virome monitoring across tick developmental stages in Shanghai will provide critical insights for early warning systems, disease prevention strategies, and public health interventions.